Old men, beards, and teachers. (Journal of Parents and Teachers, 2025)
The article refers to elderly people and the respect that some individuals have merely because they are older and have beards, drawing a parallel to teachers. It also highlights that, a few years ago, students admired their professors, whereas now they are much more distanced from this reality.